BETWEEN EMANCIPATION AND PROTECTION: THE LIMITS OF AUTONOMY FOR VULNERABLE GROUPS FROM A TRANSFORMATIVE CONSTITUTIONAL PERSPECTIVE - Magalhães, José Carlos Ferreira; Sparemberger, Raquel Fabiana Lopes (Seven Editora, 2026)
This article analyzes the tensions between autonomy and the protection of vulnerable subjects, especially children, adolescents, young people, the elderly, and people with disabilities, in light of transformative constitutionalism. Starting from human dignity and Fineman's theory of vulnerability, it examines the normative shaping of civil capacity after the Convention on the Rights of Persons with Disabilities, the Statute of Persons with Disabilities, and the 2015 Code of Civil Procedure. Empirical data from the National Council of Justice (CNJ) and decisions of the Superior Court of Justice (STJ) reveal the gap between the normative promise and the reality. It argues for the need for structural criteria to effectively balance autonomy, guardianship, and supported decision-making, avoiding both paternalism and abandonment.